Autonomy and morality: legal pluralism factors impacting sustainable natural resource management among miraa farmers in Nyambene Hills, Kenya. Issue 3 (1st September 2016) - Krueger, James S.
ABSTRACT: Natural resource management institutions overlap in rural areas, particularly in the Global South. These institutions include state agencies, officials implementing state laws of property and resource use, informal authorities with local legitimacy, and new participatory institutions like community forest associations. For some scholars, their fractious interactions, often denoted as "legal pluralism, " present a problem for sustainable resource management. Others have pointed out the potential benefits of pluralism for sustainability, such as flexibility in response to social and environmental changes. This article attempts to open up this debate by applying a pragmatic legal pluralism analysis – analyzing the history and cultural context for legal pluralism among miraa farmers in Nyambene, Kenya. Miraa is a legal but sometimes criticized stimulant that, because of government neglect, has provided space in Nyambene for some informal natural resource management. Looking at the dynamic over time between state law and local institutions in Nyambene, it is possible to tease out two factors that are key to connecting legal pluralism and sustainable behaviors. These two factors are institutions' semi-autonomy (the ability to make and enforce their own rules within legal constraints) and their moral rewards (the ability to promote individuals for adherence to a moral code).